IV Noite Cultural - Silvério, Agda Rodrigues Rios; Xavier, Eliene; Botassim, Rosa Maria Ferreira; Oliveira, Vera Lúcia Gonçalves de (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf